The Solubility of Nickel on Mixed Ultramafic Soil with Peat Soil at Saturated and Unsaturated Water Condition - Simbolon, David Ricardo; Sumawinata, Basuki; Djajakirana, Gunawan (Jurnal Ilmu Tanah dan Lingkungan, 2023)
Tropical peat with low bulk density affects the ability of peat soil to support plant growth. To improve the bulk density of peat, mineral soil is mixed to peat soil. However, mineral soil sources near peatlands are typically ultrabasic parent material with high nickel (Ni) content up to 5000 ppm. The acidic peat condition and low topography of peatlands may increase the solubility of Ni if in flooding condition. Therefore, mixing soil materials and water treatments are aimed at measuring Ni solubility at pH equilibrium after mixing and extracting using NH4OAc 1.0 N pH 7.0; 4.8; 4.2, HCl 1.0 N; 0.1 N, and H2SO4 1.0 N. The pH equilibrium after mixing soil materials was at pH 5.2-6.1, indicating Ni solubility is shown by the results of NH4OAc 1.0 N pH 7.0 - 4.8 extraction. Within this pH range, the Ni solubility value in the saturation (J) and drying (K) treatments did not differ significantly at a 5% level of significance. However, the Ni solubility with each addition of peat weight differed significantly under the saturated and moist-dried conditions (JK).